Base film for composite current collector and preparation method of base film

By adopting a sandwich structure base film of polymer polar material layer-polymer reinforced material layer-polymer polar material layer, the problem of insufficient structural stability and electrolyte resistance of composite fluid collection is solved, and the electrolyte resistance, strength and temperature resistance of the base film is greatly improved.

CN119590062APending Publication Date: 2025-03-11四川东方绝缘材料股份有限公司

Patent Information

Application Number
CN202411522007.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-03-11

Smart Images

  • Figure BDA0005108261180000061
    Figure BDA0005108261180000061
  • Figure BDA0005108261180000071
    Figure BDA0005108261180000071
Patent Text Reader

Abstract

The invention discloses a base membrane for a composite current collector and a preparation method of the base membrane, and belongs to the technical field of current collectors for lithium batteries. Comprising two polymer polar material layers and a polymer reinforcing material layer located between the two polymer polar material layers. The polymer polar material layer comprises polyolefin, a polar polymer material, an amphoteric material and an antioxidant; the polymer reinforced material layer comprises polyolefin, a reinforced material and an antioxidant; the base film for the composite current collector is of a sandwich structure composed of the polymer polar material layer, the polymer reinforcing material layer and the polymer polar material layer, the performance of the edge layer and the performance of the core layer can be considered to the maximum extent, good temperature resistance, tensile strength and electrolyte resistance are achieved, the safety of a device is improved on the whole, and the service life of the device is prolonged. And the current collector development trend is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of current collectors for lithium batteries, and in particular is a base film for composite current collectors and a preparation method thereof. Background Art

[0002] Since metal materials have good electrical conductivity, traditional current collectors use foils made of pure metal. According to the positive and negative electrode potentials of lithium batteries, aluminum foil is used for the positive electrode and copper foil is used for the negative electrode. However, with the development of technology, the metal electrodes in traditional technology can no longer fully meet the use requirements. The main problem is to balance the contradiction between the thickness of the current collector and the mechanical strength. When the thickness is reduced, the thickness of the active material on the surface coating of the current collector increases, the battery energy density will increase, but the mechanical strength will be smaller, and the current collector will be easily deformed; the current collector of the metal electrode will produce larger burrs, and the risk of battery short circuit or battery puncture is higher, which will lead to a decrease in the safety performance of the battery.

[0003] With the further development of new energy battery technology, composite copper foil has received wide attention from upstream and downstream industries. At present, composite copper foil is based on PET, PP or PI. Magnetron sputtering is first used on the surface of a film with a thickness of 4 to 6 microns to prepare a 20-80nm metal film layer; then water electroplating is used to thicken the copper layer to 1 to 5 microns. The overall thickness of the composite copper foil is 5 to 8 microns, replacing traditional copper foil. Composite copper foil can save about 70% of copper, reduce material costs, and solve problems such as reduced strength and burrs caused by thinning.

[0004] However, for the above composite current collector, since the surface polarity of the polymer film used is weak, its surface tension is low, and the surface adhesion performance is weak, the bonding force between the polymer base film and the metal layer in the prepared composite current collector is weak. On the other hand, the electrolyte resistance of the dough material is poor. After long-term use, the polymer material of the prepared composite current collector will dissolve, the metal layer will fall off, and the electrolyte will be contaminated, resulting in poor structural stability of the composite current collector, affecting the normal use of the composite current collector.

[0005] Therefore, it is extremely important to develop a composite current collector with stable structure and good electrolyte resistance, so as to improve the structural stability of the current composite current collector and promote the promotion and application of composite copper foil current collector. Summary of the invention

[0006] The object of the present invention is to provide a base film for a composite current collector and a preparation method thereof. The base film for a composite current collector has excellent electrolyte resistance, strength, temperature resistance, etc., and can meet the development trend of current collectors.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A composite current collector base film comprises two polymer polar material layers and a polymer reinforcing material layer located between the two polymer polar material layers; that is, the composite current collector base film is a sandwich structure consisting of polymer polar material layer-polymer reinforcing material layer-polymer polar material layer.

[0009] The polymer polar material layer includes polyolefin, polar polymer material, amphoteric material and antioxidant;

[0010] The polymer reinforcement material layer includes polyolefin, reinforcement material and antioxidant.

[0011] In the above scheme, by adjusting the types of components in the side layer (i.e., the polymer polar material layer), the side layer has good surface adhesion and can be well combined with metal materials. By adjusting the types of components in the core layer (i.e., the polymer reinforcement material layer), the core layer has better temperature resistance and strength than ordinary polypropylene film, so that the overall strength of the base film is increased, which is conducive to later processing and application. Compared with the prior art, the composite current collector base film prepared by the present invention is significantly improved in terms of electrolyte resistance, strength, temperature resistance, etc., meeting the development trend of current collectors.

[0012] As some possible implementation modes of the present application, the polyolefins in the polymer polar material layer and the polymer reinforcement material layer are one or more of polypropylene, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer, poly-1-butene, poly-4-methyl-1-pentene, and cycloolefin polymer.

[0013] As some possible implementation methods of the present application, the polar polymer material is one or more of polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, polydiphenyl ether sulfone, polyvinylidene chloride, polycaprolactam, polydecene formamide, polyhexamethylene sebacamide, polynonylene urea, and poly[bis(trichlorinated)ethoxy]phosphazene.

[0014] As some possible implementation modes of the present application, the amphoteric material is one or more of maleic anhydride grafted PP, MAH grafted PP, GMA grafted PP, maleic anhydride grafted PE, MAH grafted PE, GMA grafted PE, maleic anhydride grafted POE, MAH grafted POE, GMA grafted POE, maleic anhydride grafted EVA, MAH grafted EVA, GMA grafted EVA, maleic anhydride grafted EPDM, MAH grafted EPDM, GMA grafted EPDM, maleic anhydride grafted SEBS, MAH grafted SEBS, GMA grafted SEBS, methyl methacrylate-glycidyl methacrylate-ethyl propylene terpolymer, maleic anhydride grafted acrylonitrile-butadiene-styrene terpolymer, styrene-maleic anhydride random copolymer or styrene-maleic anhydride copolymer.

[0015] As some possible implementation methods of the present application, the reinforcing material is one or more of carbon nanotubes, carbon fibers, silicon carbide whiskers, glass fibers, calcium silicate whiskers, wollastonite, brucite, pyrophyllite, talc, calcium carbonate, silicon dioxide, alum, titanium dioxide, calcium oxide, magnesium oxide, carbon black, mica, etc., fatty carboxylic acid metal compounds, sorbitol benzyl derivatives, aromatic carboxylic acid metal compounds, organic phosphates and lignin acids and their derivatives, sodium benzoate and bis(p-tert-butylbenzoic acid)carboxyaluminum.

[0016] As some possible implementation methods of the present application, the antioxidants in the polymer polar material layer and the polymer reinforcement material layer are one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester, tris(2,3-di-tert-butylphenyl) phosphite, and bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite.

[0017] As some possible implementation methods of the present application, the thickness of the composite current collector base film is 4 to 6 μm, and the thickness of the polymer reinforcement material layer is 50% to 90% of the thickness of the composite current collector base film. Preferably, the thickness of the composite current collector base film is 4 to 5 μm, and the thickness of the polymer reinforcement material layer is 60% to 80% of the thickness of the composite current collector base film.

[0018] As some possible implementation methods of the present application, the polymer polar material layer includes 50 to 95 parts by mass of polyolefin, 5 to 40 parts by mass of polar polymer material, 0.1 to 10 parts by mass of amphoteric material and 0.1 to 0.5 parts by mass of antioxidant.

[0019] As some possible implementation methods of the present application, the polymer reinforcement material layer includes 89.5 to 99.8 parts by mass of polyolefin, 0.1 to 10 parts by mass of reinforcement material and 0.1 to 0.5 parts by mass of antioxidant.

[0020] In order to achieve the above object, the present invention also provides a method for preparing a composite current collector base film, comprising the following steps:

[0021] S1. Preparation of polymer polar material: firstly, polyolefin, polar polymer material, amphoteric material and antioxidant are uniformly mixed, then granulated by a twin-screw extruder granulator, and finally water-cooled, air-cooled and pelletized to obtain polymer polar material.

[0022] S2. Preparation of polymer reinforcement material: first, the polyolefin, the reinforcement material and the antioxidant are uniformly mixed, then granulated by a twin-screw extruder granulator, and finally water-cooled, air-cooled and pelletized to obtain a polymer reinforcement material;

[0023] S3. Preparation of base film for composite current collector: firstly, slice the polymer polar material and the polymer reinforcing material and dry them at 80-110°C for 4-10h; then, feed the dried polymer polar material slices into a three-layer co-extrusion side layer extruder, and feed the polymer reinforcing material slices into a three-layer co-extrusion core layer extruder, after melt extrusion, chilled by 40-110°C chilling rollers, and then sequentially stretched longitudinally, stretched transversely and shaped to obtain the base film for composite current collector.

[0024] As some possible implementation methods of the present application, in steps S1 and S2, the extrusion temperature of the twin-screw extruder granulator is 150°C to 300°C; in step S3, the extruder temperature is 150°C to 300°C

[0025] As some possible implementation methods of the present application, in step S3, the specific steps after cooling by the chilling roller are:

[0026] After being preheated at 40-120°C by the longitudinal stretching system, longitudinally stretched 2-7 times at 120-160°C, and fixed at 130-180°C, it is sent to the transverse stretching system, preheated at 80-150°C, transversely stretched 2-8 times at 140-190°C, and fixed at 140-200°C to obtain a base film for a composite current collector with a thickness of 4μm to 6μm.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention provides a composite current collector base film, which is a sandwich structure composed of a polymer polar material layer-a polymer reinforcing material layer-a polymer polar material layer, which can take into account the performance of the edge layer and the core layer to the greatest extent, and has good temperature resistance and electrolyte resistance. Among them, adding polar materials to the edge layer structure can make the edge layer have better polarity, effectively improve the surface tension, and facilitate the later composite with metal materials; adding amphoteric materials to the edge layer structure can well fuse polyolefins and polar materials together, so that the material as a whole shows uniform polarity; adding amphoteric materials and polyolefins to the edge layer structure can well bond the edge layer and the core layer together to prevent undesirable phenomena such as stratification. The introduction of strong polar substances and amphoteric substances in the edge layer can effectively stabilize the structure, thereby preventing damage to the device. Adding reinforcing substances to the core layer structure can accelerate the crystallization of polyolefins, thereby improving the temperature resistance, strength and chemical resistance of the composite current collector base film, and improving the safety of the device as a whole. DETAILED DESCRIPTION

[0029] Part 1: Preparation of polymer polar materials (Examples 1 to 4)

[0030] Example 1

[0031] All materials are pre-dried, and 90 parts by weight of polypropylene, 8 parts by weight of polyethylene terephthalate, 1.8 parts by weight of maleic anhydride grafted PP and 0.2 parts by weight of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] are mixed in a high-speed mixer at 300 rpm for 5 minutes, and granulated in a twin-screw extruder granulator at an extrusion temperature of 270±5° C. and an extruder speed of 120 rpm. The mixture is water-cooled, air-cooled and cut into granules to obtain a polymer polar material (1).

[0032] Example 2

[0033] All materials are pre-dried, and 70 parts by mass of polypropylene, 30 parts by mass of polycaprolactam, 8 parts by mass of GMA-grafted PP and 0.5 parts by mass of tris(2,3-di-tert-butylphenyl) phosphite are mixed in a high-speed mixer at 200 rpm for 5 minutes, and granulated in a twin-screw extruder granulator at an extrusion temperature of 240±5° C. and an extruder speed of 120 rpm. The polymer polar material (2) is obtained by water cooling, air cooling and cutting into granules.

[0034] Example 3

[0035] All materials are pre-dried, and 60 parts by mass of poly-4-methyl-1-pentene, 29.6 parts by mass of polymethyl methacrylate, 10 parts by mass of GMA-grafted POE, 0.3 parts by mass of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 0.1 parts by mass of tris(2,3-di-tert-butylphenyl) phosphite are mixed in a high-speed mixer at 180 rpm for 4 minutes, and then granulated in a twin-screw extruder granulator at an extruder temperature of 250±5° C. and an extruder speed of 130 rpm, and then water-cooled, air-cooled and cut into granules to obtain a polymer polar material (3).

[0036] Example 4

[0037] All materials are pre-dried, and 70 parts by mass of polyethylene, 20 parts by mass of polyvinyl alcohol, 10 parts by mass of maleic anhydride grafted POE, 0.3 parts by mass of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 0.1 parts by mass of tris(2,3-di-tert-butylphenyl) phosphite are mixed in a high-speed mixer at 180 rpm for 4 minutes, and then granulated in a twin-screw extruder granulator at an extruder temperature of 160±5° C. and an extruder speed of 80 rpm, and then water-cooled, air-cooled, and cut into granules to obtain a polymer polar material (4).

[0038] Part II: Preparation of polymer reinforced materials (Examples 5 to 7)

[0039] Example 5

[0040] All materials were pre-dried, and 98.8 parts by mass of polypropylene, 1 part by mass of silicon carbide whiskers, and 0.2 parts by mass of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate were mixed in a high-speed mixer at 200 rpm for 3 minutes, and granulated in a twin-screw extruder granulator at an extruder temperature of 200±5° C. and an extruder speed of 120 rpm. The polymer reinforced material (5) was obtained by water cooling, air cooling, and cutting into granules.

[0041] Example 6

[0042] All materials were pre-dried, and 97.9 parts by mass of polypropylene, 2 parts by mass of a fatty carboxylic acid metal compound, and 0.1 parts by mass of tris(2,3-di-tert-butylphenyl) phosphite were mixed in a high-speed mixer at 200 rpm for 3 minutes, and granulated in a twin-screw extruder granulator at an extruder temperature of 220±5° C. and an extruder speed of 150 rpm. The polymer reinforced material (6) was obtained by water cooling, air cooling, and cutting into granules.

[0043] Example 7

[0044] All materials were pre-dried, and 99.2 parts by mass of polyethylene, 0.5 parts by mass of organic phosphate, and 0.3 parts by mass of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite were mixed in a high-speed mixer at 300 rpm for 5 minutes, and granulated in a twin-screw extruder granulator at an extruder temperature of 160±5°C and an extruder speed of 145 rpm. The polymer reinforced material (7) was obtained by water cooling, air cooling, and cutting into granules.

[0045] Part 3: Preparation of composite current collector base film (Examples 8 to 11)

[0046] Example 8

[0047] The dried polymer polar material (1) is fed into a three-layer co-extrusion side layer extruder, the side layer extruder temperature is 250±5°C, the polymer reinforcement material (5) is fed into a three-layer co-extrusion core layer extruder, the core layer extruder temperature is 240±5°C, the extrusion thickness ratio of each side layer to the core layer material is 1:4, the material is melt extruded, cooled by a chill roller at 80°C, and then preheated at 120°C by a longitudinal stretching system, longitudinally stretched 5 times at 140°C, and shaped at 150°C, and then sent to a transverse stretching system, preheated at 150°C, transversely stretched 7 times at 170°C, and shaped at 175°C, to obtain a base film for a composite current collector with a thickness of 4μmm.

[0048] Example 9

[0049] The dried polymer polar material (2) is put into a three-layer co-extrusion side layer extruder, the temperature of the side layer extruder is 240±5°C, and the polymer reinforcement material (6) is put into a three-layer co-extrusion core layer extruder, the extruder temperature is 240±5°C, the ratio of the side layer to the core layer material is 1:2, the material is melt-extruded, cooled by a 90°C chill roller, and then sent to a transverse stretching system after preheating at 120°C, longitudinally stretched 6 times at 145°C, and fixed at 150°C. After that, it is sent to a transverse stretching system, preheated at 150°C, transversely stretched 7 times at 170°C, and fixed at 175°C, a base film with a thickness of 4.5μmm for a composite current collector is obtained.

[0050] Example 10

[0051] The dried polymer polar material (1) is put into a three-layer co-extrusion side layer extruder, the temperature of the side layer extruder is 250±5°C, and the polymer reinforcement material (6) is put into a three-layer co-extrusion core layer extruder, the temperature of the extruder is 240±5°C, the ratio of each side layer to the core layer material is 1:3, the material is melt-extruded, cooled by a 60°C chilling roller, and then sent to a transverse stretching system after preheating at 120°C, longitudinally stretched 5 times at 135°C, and fixed at 150°C. After that, it is sent to a transverse stretching system, preheated at 150°C, transversely stretched 7 times at 165°C, and fixed at 175°C, a base film with a thickness of 5μmm for a composite current collector is obtained.

[0052] Embodiment 11

[0053] The dried polymer polar material (2) is put into a three-layer co-extrusion side layer extruder, the temperature of the side layer extruder is 240±5°C, and the polymer reinforcement material (5) is put into a three-layer co-extrusion core layer extruder, the extruder temperature is 240±5°C, the ratio of each side layer to the core layer material is 1:3, the material is melt-extruded, cooled by a chill roller at 85°C, and then sent to a transverse stretching system after preheating at 125°C, longitudinally stretched 7 times at 145°C, and fixed at 150°C. After that, it is sent to a transverse stretching system, preheated at 150°C, transversely stretched 5 times at 175°C, and fixed at 175°C, a base film with a thickness of 6μmm for a composite current collector is obtained.

[0054] Example 12

[0055] The dried polymer polar material (3) is put into a three-layer co-extrusion side layer extruder, the temperature of the side layer extruder is 245±5°C, and the polymer reinforcement material (5) is put into a three-layer co-extrusion core layer extruder, the extruder temperature is 240±5°C, the ratio of each side layer to the core layer material is 1:4, the material is melt-extruded, cooled by a quenching roller at 80°C, and then sent to a transverse stretching system after preheating at 130°C, longitudinally stretched 5 times at 145°C, and fixed at 150°C. It is then sent to a transverse stretching system, preheated at 155°C, transversely stretched 7 times at 170°C, and fixed at 175°C to obtain a base film for a composite current collector with a thickness of 5μmm.

[0056] Example 13

[0057] The dried polymer polar material (3) is put into a three-layer co-extrusion side layer extruder, the temperature of the side layer extruder is 245±5°C, and the polymer reinforcement material (6) is put into a three-layer co-extrusion core layer extruder, the temperature of the extruder is 240±5°C, the ratio of each side layer to the core layer material is 1:3, the material is melt-extruded, cooled by a quenching roller at 85°C, and then sent to a transverse stretching system after preheating at 125°C, longitudinally stretched 6 times at 140°C, and fixed at 150°C. After that, it is sent to a transverse stretching system, preheated at 150°C, transversely stretched 7 times at 175°C, and fixed at 175°C, a base film with a thickness of 4μmm for a composite current collector is obtained.

[0058] Embodiment 14

[0059] The dried polymer polar material (3) is put into a three-layer co-extrusion side layer extruder, the temperature of the side layer extruder is 245±5°C, and the polymer reinforcement material (7) is put into a three-layer co-extrusion core layer extruder, the temperature of the extruder is 160±5°C, the ratio of each side layer to the core layer material is 1:4, the material is melt-extruded, cooled by a 60°C chill roller, and then sent to a transverse stretching system after preheating at 90°C, longitudinally stretched 5 times at 120°C, and fixed at 140°C. After that, it is sent to a transverse stretching system, preheated at 140°C, transversely stretched 7 times at 145°C, and fixed at 145°C, a base film with a thickness of 6μmm for a composite current collector is obtained.

[0060] Embodiment 15

[0061] The dried polymer polar material (4) is put into a three-layer co-extrusion side layer extruder, the temperature of the side layer extruder is 160±5°C, and the polymer reinforcement material (7) is put into a three-layer co-extrusion core layer extruder, the extruder temperature is 160±5°C, the ratio of each side layer to the core layer material is 1:3, the material is melt-extruded, cooled by a 50°C chill roller, and then sent to a transverse stretching system after preheating at 90°C, longitudinally stretched 5 times at 120°C, and fixed at 125°C. It is sent to a transverse stretching system, preheated at 135°C, transversely stretched 7 times at 140°C, and fixed at 145°C to obtain a base film for a composite current collector with a thickness of 4μmm.

[0062] The properties of the composite current collector base films prepared in Examples 8 to 15 are shown in Table 1.

[0063] Table 1:

[0064]

[0065]

[0066] Note: (1) Tensile strength test is in accordance with GB / T 13542.2-2021 Electrical insulation film Part 2, Test method. MD stands for longitudinal direction and TD stands for transverse direction.

[0067] (2) Heat shrinkage: The heat shrinkage in the longitudinal and transverse directions is tested at 120°C for 10 minutes. MD stands for longitudinal direction and TD stands for transverse direction.

[0068] (3) Electrolyte resistance: The copper-clad film is placed in the electrolyte, vacuumed, and soaked at 60°C. The discoloration of the electrolyte is observed. The darker the color, the greater the effect of the film on the electrolyte, that is, the darker the color, the worse the effect. The good, relatively good, and poor in Table 1 are all relative comparisons between the embodiments. From the data in Table 1, it can be seen that although there are many materials that we can choose and can be freely matched, not all combinations can achieve temperature resistance, strength, electrolyte resistance, and copper coating capabilities (bonding with tape, then peeling off to see the detachment, the good, relatively good, and poor in Table 1 are all relative comparisons between the embodiments).

[0069] In Examples 12-14, PMMA is added to the system, which increases the brittleness of the material. PMMA itself has low strength, and the elongation at break of the material also reduces its overall strength accordingly, which is not conducive to the subsequent copper coating process. In Example 15, materials with poor temperature resistance such as PVA and PE are present in the system, so the overall temperature resistance of the material is poor, which makes it impossible to carry out the subsequent copper coating process at 150°C or even higher temperatures. In comparison, in Examples 8-11, materials with high temperature resistance and strength are selected, which is conducive to improving the overall temperature resistance and strength of the material. At the same time, the addition of materials such as compatibilizers and strengthening aids also greatly improves the temperature resistance, strength, and electrolyte resistance of the final film.

Claims

1. A composite current collector base film, characterized in that: The invention comprises two layers of polymer polar material and a polymer reinforcing material layer located between the two layers of polymer polar material; The polymer polar material layer includes polyolefin, polar polymer material, amphoteric material and antioxidant; The polymer reinforcement material layer includes polyolefin, reinforcement material and antioxidant.

2. A composite current collector base film according to claim 1, characterized in that: The polyolefin is one or more of polypropylene, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer, poly-1-butene, poly-4-methyl-1-pentene, and cycloolefin polymer.

3. A composite current collector base film according to claim 1, characterized in that: The polar polymer material is one or more of polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, polydiphenyl ether sulfone, polyvinylidene chloride, polycaprolactam, polydecylene formamide, polyhexamethylene sebacamide, polynonylene urea, and poly[bis(trichlorinated)ethoxy]phosphazene.

4. A composite current collector base film according to claim 1, characterized in that: The amphoteric material is one or more of maleic anhydride grafted PP, MAH grafted PP, GMA grafted PP, maleic anhydride grafted PE, MAH grafted PE, GMA grafted PE, maleic anhydride grafted POE, MAH grafted POE, GMA grafted POE, maleic anhydride grafted EVA, MAH grafted EVA, GMA grafted EVA, maleic anhydride grafted EPDM, MAH grafted EPDM, GMA grafted EPDM, maleic anhydride grafted SEBS, MAH grafted SEBS, GMA grafted SEBS, methyl methacrylate-glycidyl methacrylate-ethyl propylene terpolymer, maleic anhydride grafted acrylonitrile-butadiene-styrene terpolymer, styrene-maleic anhydride random copolymer or styrene-maleic anhydride copolymer.

5. The composite current collector base film according to claim 1, characterized in that: The reinforcing material is one or more of carbon nanotubes, carbon fibers, silicon carbide whiskers, glass fibers, calcium silicate whiskers, wollastonite, brucite, pyrophyllite, talc, calcium carbonate, silicon dioxide, alum, titanium dioxide, calcium oxide, magnesium oxide, carbon black, mica, etc., fatty carboxylic acid metal compounds, sorbitol benzyl derivatives, aromatic carboxylic acid metal compounds, organic phosphates, lignin acids and their derivatives, sodium benzoate and bis(p-tert-butylbenzoic acid)carboxyaluminum.

6. The composite current collector base film according to claim 1, characterized in that: The thickness of the composite current collector base film is 4-6 μm, and the thickness of the polymer reinforcement material layer is 50%-90% of the thickness of the composite current collector base film.

7. The composite current collector base film according to claim 1, characterized in that: The polymer polar material layer includes 50-95 parts by weight of polyolefin, 5-40 parts by weight of polar polymer material, 0.1-10 parts by weight of amphoteric material and 0.1-0.5 parts by weight of antioxidant.

8. The composite current collector base film according to claim 1, characterized in that: The polymer reinforcement material layer comprises 89.5 to 99.8 parts by weight of polyolefin, 0.1 to 10 parts by weight of reinforcement material and 0.1 to 0.5 parts by weight of antioxidant.

9. A method for preparing a composite current collector base film according to any one of claims 1 to 8, characterized in that: The steps include: S1. Preparation of polymer polar material: firstly, polyolefin, polar polymer material, amphoteric material and antioxidant are uniformly mixed, then granulated by a twin-screw extruder granulator, and finally water-cooled, air-cooled and pelletized to obtain polymer polar material. S2. Preparation of polymer reinforcement material: first, the polyolefin, the reinforcement material and the antioxidant are uniformly mixed, then granulated by a twin-screw extruder granulator, and finally water-cooled, air-cooled and pelletized to obtain a polymer reinforcement material; S3. Preparation of base film for composite current collector: firstly dry the polymer polar material and the polymer reinforcing material; then put the dried polymer polar material slices into a three-layer co-extrusion side layer extruder, and put the polymer reinforcing material slices into a three-layer co-extrusion core layer extruder, after melt extrusion, they are cooled by chilled rollers, and then longitudinally stretched, transversely stretched and shaped in sequence to obtain the base film for composite current collector.

10. The method for preparing a composite current collector base film according to claim 9, characterized in that: In steps S1 and S2, the extrusion temperature of the twin-screw extruder granulator is 150°C to 300°C; in step S3, the extruder temperature is 150°C to 300°C.

Citation Information

Patent Citations

  • Composite polymer film, manufacturing method thereof, metalized composite polymer film and application

    CN115447248A

  • Multilayer composite current collector

    CN116314841A

  • Composite current collector bottom membrane, preparation method and composite current collector

    CN116581299A

  • Composite current collector for lithium ion battery as well as preparation method and application of composite current collector

    CN118156511A

  • Multilayer composite polypropylene material, and preparation method therefor and use thereof

    WO2024104393A1

Cited By

  • Dynamic self-repairing degradation-resistant composite current collector BOPET film and preparation method thereof

    CN120757831A

  • Dynamic self-healing degradation-resistant composite current collector bopet film and method of making

    CN120757831B